1972
DOI: 10.1002/ijc.2910100208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the group‐specific (gs) antigen and infectious virus expressions of the murine C‐type RNA viruses during the life span of BALB/cCr mice

Abstract: The prevalence of C-type RNA tumor-virus gs antigen and infectious virion expression was determined at various ages throughout the life span of the BALBIcCr mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…Our results with BALB/c mice are very similar to those of Peters et al (23,24), who found the same pattern of late appearance of N-tropic MuLV in these mice. They also observed that older BALB/c mice (18-33 mo of age) produce predominantly B-tropic MuLV.…”
Section: Discussionsupporting
confidence: 92%
“…Our results with BALB/c mice are very similar to those of Peters et al (23,24), who found the same pattern of late appearance of N-tropic MuLV in these mice. They also observed that older BALB/c mice (18-33 mo of age) produce predominantly B-tropic MuLV.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, histological studies have indicated no infiltration of such cells in brain of leukemic mice [Jaenisch et al, 1975]. The possibility of infection of liver and brain with MuLV produced in the thy mus tumor is also a possibility, but quantita tion of virus DNA in different tissues of leu kemic animals has indicated that horizontal infection is not likely [Baida and Drahan, 1972;Berns and Jaenisch, 1976], A close association of endogenous MuLV and globin gene expression has been reported in erythroleukemia cells [Sa/o et al, 1971;Peters et al, 1972;Dube et al, 1975;Coletta et al, 1979] and in chicken fibroblasts [Groudine and Weintraub, 1975], However, the results presented in this paper indicate no age-dependent linkage in the expression of these genes in thymus, brain or liver of AKR mice. Since Getz et al [1977] observed se lective enhancement of endogenous MuLV expression in AKR embryo cells after chemi cal transformation without any detectable globin RNA, it might be that the integrated position of the virus in host genome in AKR cells is different from that in Friend cells [zlstrin, 1978;Jahner and Jaenisch, 1980].…”
Section: Discussionmentioning
confidence: 99%
“…Murine leukemia virus (MuLV) exists as a genetic infection in all mice (7,8), and although genes of these endogenous viruses are not normally expressed in young adults of low leukemic strains (9)(10)(11)(12), MuLV antigens can often be detected in chemically induced tumors (13,14). Since mice of most strains are able to make antibodies against envelope antigens of their endogenous MuLV (15)(16)(17), it is conceivable that the crossreacting antibodies formed against chemically induced tumors are, in fact, a response to MuLV antigens that are expressed by some of them.…”
mentioning
confidence: 99%